Angioedema Related to Angiotensin-Converting Enzyme Inhibitors: Attack Severity, Treatment, and Hospital Admission in a Prospective Multicenter Study. Issue 45 (November 2015) - Javaud, Nicolas; Achamlal, Jallal; Reuter, Paul-George; Lapostolle, Frédéric; Lekouara, Akim; Youssef, Mustapha; Hamza, Lilia; Karami, Ahmed; Adnet, Frédéric; Fain, Olivier
Abstract : Abstract: The number of cases of acquired angioedema related to angiotensin converting enzyme inhibitors induced (ACEI-AAE) is on the increase, with a potential concomitant increase in life-threatening attacks of laryngeal edema. Our objective was to determine the main characteristics of ACEI-AAE attacks and, in doing so, the factors associated with likelihood of hospital admission from the emergency department (ED) after a visit for an attack. A prospective, multicenter, observational study (April 2012–December 2014) was conducted in EDs of 4 French hospitals in collaboration with emergency services (SAMU 93) and a reference center for bradykinin-mediated angioedema. For each patient presenting with an attack, emergency physicians collected demographic and clinical presentation data, treatments, and clinical course. They recorded time intervals from symptom onset to ED arrival and to treatment decision, from ED arrival to specific treatment with plasma-derived C1-inhibitor (C1-INH) or icatibant, and from specific treatment to onset of symptom relief. Attacks requiring hospital admission were compared with those not requiring admission. Sixty-two eligible patients with ACEI-AAE (56% men, median age 63 years) were included. Symptom relief occurred significantly earlier in patients receiving specific treatment than in untreated patients (0.5 [0.5–1.0] versus 3.9 [2.5–7.0] hours; P  < 0.0001). Even though icatibant was injected more promptly than plasma-derived C1-INH, there, however, was no significant difference in median time to onset of symptom relief between the 2 drugs (0.5 [0.5–1.3] versus 0.5 [0.4–1.0] hours for C1-INH and icatibant, respectively, P  = 0.49). Of the 62 patients, 27 (44%) were admitted to hospital from the ED. In multivariate analysis, laryngeal involvement and progressive swelling at ED arrival were independently associated with admission (Odds ratio [95% confidence interval] = 6.2 [1.3–28.2] and 5.9 [1.3–26.5], respectively). A favorable course was observed in all patients. Three patients (5%) experienced a recurrence after angiotensin-converting enzyme inhibitor discontinuation after a median follow-up of 18 (11–30) months. Two severity criteria—laryngeal edema and the progression of the edema—were independent factors associated with likelihood of hospital admission. Appropriate specific treatments (plasma-derived C1-INH or icatibant) should be available in EDs to prevent possibly life-threatening complications.